THE ROLE OF VISUAL ARTS IN VEDIC AND UPANISHAD THOUGHT - A HISTORICAL ANALYSIS - Mishra, Sanjeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has made a profound contribution to metaphysical thought, particularly through the Vedas and Upanishads, which are revered as much for their spiritual depth as for their philosophical inquiries. These ancient texts address fundamental questions about existence, reality, and the nature of consciousness. The Katha Upanishad, for instance, explores the eternal and conscious essence within transient beings, stating: "There is one who is the eternal reality among non-eternal objects, the one truly conscious entity among conscious objects, and who, though non-dual, fulfils the desires of many. Eternal peace belongs to the wise who perceive him within themselves." Such passages reflect a deep-seated curiosity about life, death, and the interconnectedness of all existence.